Effect of La3+ ion substitution on the dielectric properties of single-crystalline BaTi2O5. Issue 17 (1st December 2017) - Shiga, Keiji; Katsui, Hirokazu; Kakuda, Hiroyuki; Yoshikawa, Kazuma; Tsuneyoshi, Jun; Goto, Takashi
Abstract: La 3+ ion substituted single-crystalline BaTi2 O5 (Ba1− x La x Ti2 O5− z ) was prepared by a floating zone method, and the effect of La 3+ ion substitution on the phase composition, microstructure and dielectric properties of Ba1− x La x Ti2 O5− z was investigated. Ba1− x La x Ti2 O5− z was a single phase of BaTi2 O5 and its growth direction was parallel to the b -axis at an La 3+ content lower than 0.9 at% ( x < 0.009). As the substitution increased from 0 to 0.9 at% La 3+, the lattice parameters a and c decreased from 1.6906 to 1.6899 nm and from 0.9411 to 0.9406 nm, respectively, and the Curie temperature decreased from 752 K to 700 K. The complex impedance plane plots of single-crystalline BaTi2 O5 at 648 K showed a single semicircle associated with the ferroelectric bulk response at high frequencies and a spike associated with ionic diffusion at low frequencies. In contrast, the complex impedance plane plots of Ba1− x La x Ti2 O5− z showed a distorted semicircle at an La 3+ content lower than 0.2 at%, while those comprised a distorted semicircle at low frequency below 10 Hz and a part of a small semicircle at high frequency (> 10 Hz) at an La 3+ content higher than 0.4 at%, indicating the predominance of electronic conduction. The remanent polarization ( P r ) of Ba1− x La x Ti2 O5− z at room temperature increased with increasing x and was as high as 7 × 10 −2 C m −2 at Ba0.996 La0.004 Ti2 O5− z .